Awareness of Agro-tourism and livelihood of the communities’ opportunities and perceived impacts in South West, Nigeria - Akintade, E. A; Amos, T.T.; Odusanya , M. D. (ADAN JOURNAL OF AGRICULTURE, 2026)
This paper assessed rural dwellers' awareness of agro-tourism and livelihood as well as the perceived impacts on their socioeconomic well-being in selected states in southwest Nigeria. The objective was to gain insight and assess awareness of agro-tourism and rural dwellers livelihoods and community opportunities as well as the palpable disparity between the perceived negative impacts of agro-tourism development in the neighboring communities to the selected states in southwest Nigeria. Strategic management, such as recreational facilities, can help to integrate earning sources and, as a result, increase farm productivity. These would rely on the efficient flow and utilization of farm resources in different events and value addition to farm output. The primary data were gathered from respondents by using personal in-depth interviews with the aid of the semi structured questionnaires. The choices of the selected states indicate convenience (cluster) not spread that could have captured the SW as a whole. The states selected were not randomly done. Data collection was carried out on a purposive sample of those initiated as were selected to represent the most central aspects of the agritourism scene of the region. The questionnaire method of data collection was employed to collect the needed empirical data. A purposive sampling and simple random sampling were used to select the respondents in the study area. To achieve this even distribution of the questionnaires across the three locations, 200 questionnaires were distributed to each state in Ekiti, Ondo and Osun making a total of 600 questionnaires that were administered evenly across the three selected states. Of all those instruments administered, 549 valid copies were retrieved and used in the final analysis of the study. The collected data were analyzed by descriptive and Inferential statistics. The results revealed agro-tourism facilities and only 65% of the potential were functional. The study also revealed that the visitors visited the places three times a week. The results also showed that 94% and 88% of the respondents kept up the green environment and the facilities, respectively. Social and economic values were found to be very strongly correlated with the sites. The foreign exchange revenues, job creation, popularity of the state, education of the locals and saving the green environment for a better living were these. The agro-tourism Centres were found to have immense potential of creating employment and income stability in the study area.